Sharing of Grant Funds between Academic Institutions and Community Partners in Community‐Based Participatory Research - Katrice D. Cain; Jacqueline R. Theurer; Ashwini R. Sehgal (Wiley, 2014)
Abstract Objectives To determine how grant funds are shared between academic institutions and community partners in community‐based participatory research (CBPR). Methods Review of all 62 investigator‐initiated R01 CBPR grants funded by the National Institutes of Health from January 2005 to August 2012. Using prespecified criteria, two reviewers independently categorized each budget item as being for an academic institution or a community partner. A third reviewer helped resolve any discrepancies. Results Among 49 evaluable grants, 68% of all grant funds were for academic institutions and 30% were for community partners. For 2% of funds, it was unclear whether they were for academic institutions or for community partners. Community partners' share of funds was highest in the categories of other direct costs (62%) and other personnel (48%) and lowest in the categories of equipment (1%) and indirect costs (7%). Conclusions A majority of CBPR grant funds are allocated to academic institutions. In order to enhance the share that community partners receive, funders may wish to specify a minimum proportion of grant funds that should be allocated to community partners in CBPR projects.